Inhibitors of human EZH2, and methods of use thereof - SCOTT MARGARET DAVIS; KUNTZ KEVIN WAYNE; POLLOCK ROY MACFARLANE; SNEERINGER CHRISTOPHER JOHN; COPELAND ROBERT ALLEN; RICHON VICTORIA MARIE; KNUTSON SARAH KATHLEEN (2016)
The invention relates to inhibition of wild-type and certain mutant forms of human histone methyltransferase EZH2, the catalytic subunit of the PRC2 complex which catalyzes the mono-through tri-methylation of lysine 27 on histone H3 (H3-K27). In one embodiment, the inhibition is selective for the mutant form of the EZH2, such that trimethylation of H3- K27, which is associated with certain cancers, is inhibited. The methods can be used to treat cancers including follicular lymphoma and diffuse large B-cell lymphoma (DLBCL). Also provided are methods for identifying small molecule selective inhibitors of the mutant forms of EZH2 and also methods for determining responsiveness to an EZH2 inhibitor in a subject. 本发明涉及对人组蛋白甲基转移酶EZH2的野生型和某些突变形式的抑制，所述EZH2是PRC2复合物的催化亚基，所述PRC2复合物催化组蛋白H3上赖氨酸27(H3?K27)的单?至三?甲基化。在个实施方式中，所述抑制对于所述EZH2的突变形式是选择性的，从而抑制与某些癌症相关的H3?K27的三甲基化。可以使用所述方法来治疗癌症，包括滤泡性淋巴瘤和弥散性大B细胞淋巴瘤(DLBCL)。本发明还提供用于鉴定EZH2突变形式的小分子选择性抑制剂的方法，以及用于测定对象内对EZH2抑制剂响应性的方法。